Criminal Liability in Artificial Intelligence-Based Medical Malpractice: Normative Voids and Challenges of Modern Health Law - Nirwan Afandy; Hasbuddin Khalid; Satrih Hasyim (Golden Ratio of Law and Social Policy Review, 2026)
This study aims to examine the construction of criminal liability in cases of medical malpractice involving artificial intelligence and to identify the normative gaps within contemporary health law that hinder effective accountability. It further seeks to formulate a responsive legal framework capable of addressing the challenges posed by the integration of advanced technologies in medical practice. The research employs normative legal methodology using statute and conceptual approaches. The statute approach analyzes existing legal provisions governing healthcare and criminal liability, while the conceptual approach explores doctrinal principles such as fault, negligence, and responsibility in technologically mediated environments. Data are analyzed using a descriptive prescriptive method to both explain current legal conditions and propose normative solutions. The findings reveal that existing legal frameworks remain anthropocentric and are unable to adequately address the distributed nature of responsibility in AI mediated healthcare. The absence of explicit regulations on the use of artificial intelligence creates a normative vacuum, leading to uncertainty in attributing criminal liability among physicians, developers, and healthcare institutions. The study also finds that traditional doctrines such as mens rea and actus reus are increasingly difficult to apply in cases where decision making involves algorithmic systems. As a result, there is a need to reconceptualize criminal responsibility through more adaptive models, including shared responsibility and selective strict liability. This research concludes that legal reform is essential to ensure accountability, legal certainty, and patient protection in the era of digital healthcare. It proposes the development of integrated and forward looking legal frameworks that align technological innovation with fundamental principles of criminal law.